Doorbell Activated Porch Light / Mohd Naim Ahmadi and Maheran Hamid - Ahmadi, Mohd Naim; Hamid, Maheran (2006)
Doorbell Activated Porch Light is important because it can help to see callers who ring our doorbell at night. The idea is that when the doorbell is pressed during the day, the bell rings as the normal but at night time, a nearby outside iamp wiil illuminate for a few minutes so we can identify who's outside. The door bell activated Porch light which is describe in this project is, light and compact. It is operated bv a doorbell switched and is small enough to place or hide anywhere. To complete this circuit mam components 1C1 741 ( op-amp), IC2 NE555(timerj, light dependent resistor, relay and NPN transistor are needed. When the switch is tumed-on at the day, the buzzer will operate as normal and the lamp will not operate. Otherwise, the light will mm on when the switch is tumed-on at night so we can see the cailers.